Hepatic Stellate Cell: A Double-Edged Sword in the Liver - Luo, Nianan; Li, Jiangbin; Wei, Yu; Lu, Jianguo; Dong, Rui (Physiological research, 2021)
Hepatic stellate cells (HSCs) are located in the space of Disse, between liver sinusoidal endothelia cells (LSECs) and hepatocytes. They have surprised and excited hepatologists for their biological characteristics. Under physiological quiescent conditions, HSCs are the major vitamin A-storing cells of the liver, playing crucial roles in the liver development, regeneration, and tissue homeostasis. Upon injury-induced activation, HSCs convert to a pro-fibrotic state, producing the excessive extracellular matrix (ECM) and promoting angiogenesis in the liver fibrogenesis. Activated HSCs significantly contribute to liver fibrosis progression and inactivated HSCs are key to liver fibrosis regression. In this review, we summarize the comprehensive understanding of HSCs features, including their roles in normal liver and liver fibrosis in hopes of advancing the development of emerging diagnosis and treatment for hepatic fibrosis.
Keywords: Hepatic Stellate Cells; játra; jaterní hvězdicovité buňky; Animals; Humans; Liver; lidé; Liver Cirrhosis; zvířata; jaterní cirhóza